1998
DOI: 10.1021/la9709857
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Scanning Tunneling Microscopy Imaging of the Reductive Desorption Process of Alkanethiols on Au(111)

Abstract: The reductive desorption process of self-assembled monolayers of 1-hexadecanethiol, 1-propanethiol, and 3-mercaptopropionic acid on Au(111) has been studied in 0.5 M KOH solution by in-situ scanning tunneling microscopy (STM) and cyclic voltammetry. In-situ STM images of the monolayers at the potentials between −0.2 V and the reduction potentials of each thiols show the pits that are commonly seen in STM images of thiol self-assembled monolayers. A drastic morphological change takes place in the STM image arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(151 citation statements)
references
References 32 publications
7
142
0
2
Order By: Relevance
“…Quantitative values of the coverage can be obtained by voltammetry [98][99][100][101][102][103][104] since electrochemical cleavage of the SAM S-Au bonds at negative potential follows reaction eqn (1). This one-electron reductive desorption process 105 should be accomplished in strongly basic solution (pH > 11) 100 to obtain precise coverage values and to avoid interference with dihydrogen evolution as well as to ascertain complete desorption.…”
Section: This Journal Is C the Owner Societies 2011mentioning
confidence: 99%
“…Quantitative values of the coverage can be obtained by voltammetry [98][99][100][101][102][103][104] since electrochemical cleavage of the SAM S-Au bonds at negative potential follows reaction eqn (1). This one-electron reductive desorption process 105 should be accomplished in strongly basic solution (pH > 11) 100 to obtain precise coverage values and to avoid interference with dihydrogen evolution as well as to ascertain complete desorption.…”
Section: This Journal Is C the Owner Societies 2011mentioning
confidence: 99%
“…Both target compounds form SAMs by binding to the gold surface via their thiolate anchor-groups. Hence, by cycling the potential applied to the gold electrode their desorption (reductive, negative potential E c ) and possibly re-adsorption (oxidative, positive potential, E a ) behavior, which occurs according to reaction (II) [69][70][71] Au À S À R þ e À Ð Au þ À S À R…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…Au -SR + e -=> Au + RS - (1) many electrochemical studies of the reaction (1) have been carried out because the peak area and the shape of the cathodic peak for the reductive desorption and its peak potential provide useful information of the SAM such as the adsorbed amount, stability, adsorption energy, orientation, and substrate morphology [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. For example, it was found that the longer the alkylchain, the more negative the reductive peak potential, reflecting the stronger van der Waals attractive interaction among alkylchains [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that the longer the alkylchain, the more negative the reductive peak potential, reflecting the stronger van der Waals attractive interaction among alkylchains [17]. The reductive desorption process has been investigated by many techniques including electrochemistry [17][18][19][20][21][22][23][24][25][26], FT-IR [27][28][29], electrochemical QCM [30][31][32], and in situ STM [33][34][35][36]. Several groups suggested the formation of an "aggregate" or "micelle" near or on the electrode surface after the reductive desorption of the SAM [28,33,35].…”
Section: Introductionmentioning
confidence: 99%